A Survey on General Health among students of guidance schools - Mousavi Moghadam, Seyyed Rahmatollah; Imanzad, Masoumeh; Tavan, Hamed; Sayemiri, Koroush; Amini, Khadijeh Soghra (Archives of Advances in Biosciences, 2014)
In recent years, the prevalence of mental disorders has increased and the prevalence of 18-23% is reported for Iran. This study aims to evaluate psychological aspect of general health status of children in Ilam city, located in Iran using a questionnaire. This study is a descriptive-comparative research that measures general health of boys and girls in schools. The required information is obtained by means of the GHQ-28 standard questionnaire which distributed among 118 children. The general health is divided into four categories, in which the dangerous group receives the higher scores in the range of 64-84. The SPSS software is used for data analysis. The sample consisted of 64 (54%) boys and 54 (46%) girls and overall score of children are classified into four categories. Among the samples, 38 participants (32.2%), 61 children (51.7%), 17 children (14.7%) and two persons (1.7%) are received the scores of 0-21, 22-42, 43-63 and 64-84, respectively. Also, the statistical association is observed between age, grade and general health of participants (P <0.05). Relatively large numbers of children possessed good general health status. It is found that as age of participant is increased its general health degrades.